2011
DOI: 10.1007/978-3-642-23629-7_60
|View full text |Cite
|
Sign up to set email alerts
|

3D Active Shape Model Segmentation with Nonlinear Shape Priors

Abstract: Abstract. The Active Shape Model (ASM) is a segmentation algorithm which uses a Statistical Shape Model (SSM) to constrain segmentations to 'plausible' shapes. This makes it possible to robustly segment organs with low contrast to adjacent structures. The standard SSM assumes that shapes are Gaussian distributed, which implies that unseen shapes can be expressed by linear combinations of the training shapes. Although this assumption does not always hold true, and several nonlinear SSMs have been proposed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…The parts are assumed to be conditionally independent of one another, an assumption that has demonstrated superior performance in computation and generalisation. This form of delineation readily allows integration with advanced feature searching techniques [12], and shape optimisation methods, e.g., a Bayesian inference [11] or density estimation [26]. However a deficiency is that as a coarse delineation none of current methods give consideration to unbiasedly utilising, encoding and reconstructing the entire object appearance.…”
Section: Object Class Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…The parts are assumed to be conditionally independent of one another, an assumption that has demonstrated superior performance in computation and generalisation. This form of delineation readily allows integration with advanced feature searching techniques [12], and shape optimisation methods, e.g., a Bayesian inference [11] or density estimation [26]. However a deficiency is that as a coarse delineation none of current methods give consideration to unbiasedly utilising, encoding and reconstructing the entire object appearance.…”
Section: Object Class Representationmentioning
confidence: 99%
“…The shape can be either bounded by a subspace constraint [36] as in standard ASMs or optimised by a regulariser using, e.g., density estimation [26,37], a Bayesian model [11], or sparse shape composition [38,39], leading to more efficient fitting. It has been shown that utilising multiple predictions of individual landmarks can result in robust fitting.…”
Section: Shape Regularisationmentioning
confidence: 99%
“…Although sophisticated algorithms have been developed (e.g., using deformable M-Reps [23] or statistical shape models [12,15,17,21]), wrongly segmented regions still occur in difficult cases. Algorithm evaluation compares reference (i.e., ground truth) and automatic segmentations, which can be in form of meshes (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Such active shape models are widely used to characterize structures in medical images [5] as well as for biomedical image segmentation [6]. There exist also variants of the technique that make use of non-linear algorithms [7].…”
Section: Introductionmentioning
confidence: 99%